Madu lebah kelulut (Trigona Spp.) dalam aktifitas terhadap bakteri Staphylococcus aureus resisten - Muhammad Ma'ruf; Gina Alia Mawaddah; Nisa Nur Agistni Eriana; Farah Indah Swari; Syaidatul Aslamiyah; Leka Lutpiatina (Jurnal Skala Kesehatan, 2018)
Infection caused by Staphylococcus aureus bacteria becomes a very serious problem because of the increased resistance of these bacteria to various types of antibiotics. Honey has antibacterial activity because it contains water, acidity and inhibitor compounds namely flavonoids. Honey can be produced Trigona spp. This study aims to Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) and effectiveness of honey bee kelulut (Trigona spp.) Against Staphylococcus aureus resistant cephalosporin bacteria in vitro. This research is true experiment with postest only control group design. The results of the study were measured by MIC showed no clarity at concentrations of 60 mg / ml, 70 mg / ml, 80 mg / ml, 90 mg / ml and and clarity at concentrations of 100 mg / ml, and MBC at concentrations of 60 mg / ml of 151 colonies, 70 mg / ml of 105 colonies, 80 mg / ml of 55 colonies, 90 mg / ml of 16 colonies and 100 mg / ml of 0 colonies. The effective concentration in killing Staphylococcus aureus resistant cephalosporin is 100 mg / ml